2020
DOI: 10.3390/nu12061897
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction among Female Patients Seeking Treatment for an Eating Disorder: Prevalence and Associated Factors

Abstract: The concept of “food addiction” (FA) has aroused much focus because of evidence for similarities between overeating and substance use disorders (SUDs). However, few studies have explored this concept among the broad spectrum of eating disorders (ED), especially in anorexia nervosa (AN). This study aimed to assess FA prevalence in ED female patients and to determine its associated factors. We recruited a total of 195 adult women with EDs from an ED treatment center. The prevalence of FA diagnosis (Yale Food Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 75 publications
5
43
0
Order By: Relevance
“…The present review suggests that it would be effective to identify FA phenotypes based on the presence of other psychiatric disorders such as ED, AUD/SUD, PTSD, depression, anxiety, and ADHD as part of a comprehensive biopsychosocial assessment, and to assign nutrition treatment based on the relative strength of the FA signal amidst the noise (true versus false positive). Recent studies have identified different phenotypic characterizations of the FA construct [ 60 , 61 , 202 , 203 ]. However, Table 1 suggests a guide for clinicians to consider in settings where the use of extensive validated instruments is not always practical.…”
Section: Discussionmentioning
confidence: 99%
“…The present review suggests that it would be effective to identify FA phenotypes based on the presence of other psychiatric disorders such as ED, AUD/SUD, PTSD, depression, anxiety, and ADHD as part of a comprehensive biopsychosocial assessment, and to assign nutrition treatment based on the relative strength of the FA signal amidst the noise (true versus false positive). Recent studies have identified different phenotypic characterizations of the FA construct [ 60 , 61 , 202 , 203 ]. However, Table 1 suggests a guide for clinicians to consider in settings where the use of extensive validated instruments is not always practical.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high attachment insecurity are more likely to use these “external regulators of affect” instead of utilizing more adaptive emotional regulation strategies. Attachment insecurity has been studied in the context of disordered eating, eating disorders, and obesity, but there is still limited research on food addiction [ 130 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 195 adult women from an eating disorder treatment center, the prevalence of food addiction was 83.6%, and the most frequently reported food addiction criteria were “clinically significant impairment or distress in relation to food”, “craving”, and “persistent desire or repeated unsuccessful attempts to cut down”. Within this sample, no differences in attachment insecurity were found between those meeting the criteria for food addiction and those who did not fulfill the criteria for food addiction [ 132 ]. As such, there may be a similarity between food addiction and eating disorders in terms of attachment patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a clinical manifestation of addiction to food, as much as 61.5% of patients with anorexia nervosa (AN) of the restrictive type were found to suffer from FA, which translates how much the addictive behavior related to food can be a common pathological dimension to all EDs, as well as a possible accompanying manifestation of other forms of behavioral addiction to fasting, physical exercising, etc. [ 12 ].…”
Section: Introductionmentioning
confidence: 99%